Variations in mitragynine content in the naturally growing Kratom (Mitragyna speciosa) population of Thailand - Leksungnoen, Nisa; Andriyas, Tushar; Ngernsaengsaruay, Chatchai; Uthairatsamee, Suwimon; Racharak, Phruet; Sonjaroon, Weerasin; Kjelgren, Roger; Pearson, Brian J.; McCurdy, Christopher R.; Sharma, Abhisheak (Frontiers in Plant Science, 2022)
We analyzed the content of mitragynine (MG) found in kratom leaves (Mitragyna speciosa) and the influence of different environmental conditions (air and soil variables) on the yield in various regions of Thailand. The content of MG in kratom leaves ranged from 7.5 – 26.6 mg g-1 of dry leaf weight. Canonical correspondence analysis showed that the most significant environmental variables affecting the MG content among the various regions were light intensity, relative humidity, soil volumetric water content (VW), soil pH, and calcium. This study is a first step towards providing information about environmental conditions suitable to maximize the quality and quantity of bioactive alkaloids in kratom. Future studies should focus on leaf collection and the post-harvest processes in order to assure the desired alkaloidal content in finished products, when produced under suitable environmental conditions identified in this study.